Changes in plasma urate concentration immediately after acute myocardial infarction. Issue 5991 (1st November 1975) - Ghosh, P; Cochrane, A M; Gordon, P W; Radcliffe, A G
Abstract : The plasma urate concentration of 70 patients with acute myocardial infarction increased progressively up to the seventh day and was significantly higher than in a group of 23 patients with ischaemic changes only. Diuretic treatment might have accounted for an early rise in urate levels but the persistent increase seen at seven days could not be so explained.